The politics of chemistry : science and power in twentieth-century Spain - Nieto-Galan, Agustí (Cambridge University Press, 2019)
Nieto-Galan examines the political role of chemistry in twentieth-century Spain, enriching understandings of the relationship between science and power.
Keywords: Chemistry -- Social aspects -- Spain -- History -- 20th century.; Chemistry -- Political aspects -- Spain -- History -- 20th century.; Science -- Social aspects -- Spain -- History -- 20th century.; Science -- Political aspects -- Spain -- History -- 20th century.; Science and state.; Chimie -- Aspect social -- Espagne -- Histoire -- 20e siècle.; Chimie -- Aspect politique -- Espagne -- Histoire -- 20e siècle.; Sciences -- Aspect social -- Espagne -- Histoire -- 20e siècle.; Sciences -- Aspect politique -- Espagne -- Histoire -- 20e siècle.; Politique scientifique et technique.; Chemistry -- Social aspects; Science and state; Science -- Political aspects; Science -- Social aspects; Spain; 1900-1999; History